Ischemic necrosis of the femoral head in dogs and some considerations in human beings - Alvarado Morillo, Manuel (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
Ischemk necrosis of the femoral head (I.N.F.H.) is a disease found primarily in small or dwarf dogs, characterized by ischemia induced necrosis and ultimate collapse of the subchondral bone in the head of the femur [15]. There is a disease in human being (Legg-calve-Perthes Syndrome) which has many similarities to the canine disease [7]. Most of the children affected are small for their age and often were born premature. The age of onset of clinical signs in children is usually between three and five years old. In dogs, the affected animals are presented at about four to ten months of age. It is likely however, that the initiating incident occurs much earlier, around 6-12 weeks of age in dogs, because it takes time for the dead bone to lose its rigidity and to, finally, collapse. In dogs, the number of males and females affected is about equal. In contrast to this, the ratio in Legg-Calve-Perthes Syndrome is four boys to one girl. An explanation advanced for this difference is that boys are more active than girls and therefore, are subject to greater trauma. In the canine, the sex of the puppy does not as greatly influence the amount of activity engaged in. Â